The Extent of Employment of Teachers of The Basic Education Stage (Second Cycle) for Networks Social Communication In The Educational Process Field Study In Lattakia - Barakat , Ghassan; Ahmad , Moteah; Shahen, Youssef (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The aim of the research is to identify the extent to which the teachers of the basic education stage (H2) in Lattakia for social networks in the educational process and the study of the differences between teachers in basic education (H2) in relation to the extent of employment of social networks in the educational process, Qualifications, years of teaching experience. The research was based on the descriptive approach. The research community included all the teachers and teachers in the basic education stage in Lattakia. The sample of the study is a random sample of (200) teachers and teachers. The questionnaire was distributed to them. The research found a number of results, the most important of which are: The teachers of the second cycle of basic education in Lattakia employ social networks (as a source of knowledge, teaching, promotion of education, evaluation) to a medium degree. The results showed that there were no statistically significant differences between the average teachers of the second cycle of basic education in Lattakia in the extent of their employment of social networks in the educational process due to gender variables, scientific qualification and years of experience.